Holocaust Survivors in Argentina during the Six-Day War in the Middle East (1967) - Kahan, Emmanuel Nicolás (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper attempts to reconstruct the actions developed by the Sherit Hapleitá Association of Survivors of the Nazi Regime in Argentina, during the Six-Day War in the Middle East. It also seeks to analyze the operation of an “Argentinian” narrative regarding this experience and the survival of Nazism as legitimating discourse for both the existence of Israel and its actions. In this sense, the interventions of Holocaust survivors were particularly meaningful because they took place in a national context in which narratives of the nationalist right and those of leftist organizations in process of radicalization, questioned the loyalty of Jews to the Argentine nationality, as well as the legitimacy of Sionism as political adscription. The research was based on the documentary archive of the president of the organization at the time, as well as a study of the written press during period.